2017
DOI: 10.1007/s13224-017-1038-8
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasonographic Placental Thickness in Prediction of Fetal Outcome: A Prospective Indian Study

Abstract: Placental thickness at 32 and 36 weeks corresponds well with gestational age and is a good prognostic factor in assessing neonatal outcome. Therefore, placental thickness should be measured in addition to biometric parameters in antenatal women undergoing ultrasound.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
32
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 10 publications
4
32
3
Order By: Relevance
“…Also, there is statistically significant relation between placental thickness second trimester and Apgar score at 5 th minute. These results support that of Nagpal et al [16] who reported that there was proportional correlation between placental thickness and Apgar score at 32 and 36 weeks.…”
Section: Disucssionsupporting
confidence: 92%
See 4 more Smart Citations
“…Also, there is statistically significant relation between placental thickness second trimester and Apgar score at 5 th minute. These results support that of Nagpal et al [16] who reported that there was proportional correlation between placental thickness and Apgar score at 32 and 36 weeks.…”
Section: Disucssionsupporting
confidence: 92%
“…Our results are in agreement with study of Adeyekun & Ikubor [9] as they reported that study subjects were 29.1 ± 4.9 years. The mean maternal weight was 71.4 ± 13.6 kg and mean height was 1.6 ± 0.5 m. Nagpal et al [16] found that, mean age of their study population was 23.1 ± 3.02 years. Majority of women were in age group of 19-23 years.…”
Section: Disucssionmentioning
confidence: 83%
See 3 more Smart Citations